(untitled) (Research, Society and Development, 2021)
Objective: To characterize the assistance provided by the Mobile Emergency Service and Fire Department to victims of motorcycle accidents in the interior of São Paulo. Method: This is a cross-sectional, documentary, retrospective, quantitative research. Data were collected through the attendance sheets for the years 2016 and 2017, and analyzed using descriptive statistical analysis. This study was approved by the Research Ethics Committee. Results: Most of the victims were male (61.3%), aged between 21 and 30 years old (38.8%), drivers (92.9%). Lower limbs (43.5%) and upper limbs (24.0%) were the most affected body regions. Most of the consultations were performed by the Basic Support Unit of the Mobile Emergency Care Service (56.6%), and were referred to the Emergency Care Unit (57.9%). Conclusion: It is considered essential to develop specific interventions such as adequate infrastructure, combined with accident prevention programs, to reverse this situation.